Numerical analysis of the vortex flow effect on the thermal-hydraulic performance of spray dryer - Fajar Anggara; Dedik Romahadi; Alief Luthfie Avicenna; Yosua Heru Irawan (Universitas Mercu Buana, 2022)
The use of a spray-dryer is very popular in the drying process in the food and beverage industry. However, due to the properties of the sensitive product that the quality will degrade in drying at high temperature, the innovative design of spray-dryer is developed which can increase the heat transfer rate at moderate temperature. This research was conducted to develop a spray-dryer design to improve thermal-hydraulic performance, with a high transfer rate and low-pressure drop at such a temperature. The design varies by several inlets categorized as design A with one inlet, design B with two inlets, and design C with three inlets. This simulation uses ANSYS FLUENT17, and the independence of the mesh was evaluated to improve the result of the simulation. The efficient mesh number is obtained from the independence of the mesh at around one million. The result shows that design C has the lowest pressure loss and the highest transfer rate due to high vortex and swirl flow generation, improving the mixture quality and direct contact between droplet and dry-air.